A EVASÃO APARENTE ENTRE ENGENHARIAS SOB A ÓTICA DA ANÁLISE DE REDES SOCIAIS - Newton da Silva Miranda Júnior (Universidade Federal de Santa Catarina, 2018)
Although high rates of academic dropout among engineering students are discussed, the so-called apparent dropout phenomenon does not get enough attention, even though they are part of the picture. Thus, the paper addresses this issue among engineering students, using a Social Network Analysis - ARS. As a general goal, we described this network through metrics such as density and degree of centrality, analyzing the migration of the 259 cases of internal transfers of students between 15 different types of engineering majors in the period ranging from 2012 to 2016 at the University from Brasilia. The dense network and the directions of the migratory flows between the courses suggest a propensity of engineering students to only change of habilitation within the field of engineering. Mechanical, electrical and production engineering have emerged as the most desired engineering careers. Also, the engineering careers created more recently at the university tended to lose students within the network. The evidences of the study allowed us to conclude that students, although uncertain about which type of engineering, have no doubts regarding the field of engineering.